Ensaio sobre a macroeconomia clássica - Costa, Karolyne Santana (2017)
This essay presents a theoretical foundation for the analysis concepción on the formation of the equilibrium between aggregate supply and aggregate demand in the classical model. To arrive at the considerations presented here, the history of classical economic thought was taken into account, drawing as a starting point the rupture of mercantilism. From this historic mark it was possible to describe the main names that were responsible for changing the economic conception during the years that followed. It was also tried to report some of the your most import contributions to the formation of orthodox ideas of the classical school, which are in force and are reformulated up to the present moment. With the construction of the theoretical and graphic model, then presents the importance and coherence coexistente in the exposed model, evidencing its impacts on the evolution of economic thinking.